Competition policy and employment: an application to Ireland - Fingleton, John (Economic & Social Studies, 1993)
This paper models an open economy with a competitive traded sector and a monopolistic non-traded sector. Competition policy in the non-traded sector can reduce the price of traded goods and increase welfare but only if the labour market clears continuously. If insider workers have "power" over entrepreneurs, competition policy merely enables wage increases (or increased profit taking) in both sectors. In general, the analysis highlights the fact that unemployment is not just a labour market phenomenon. Competition policy may be cumulative in its effect so that the returns are more likely to be realised in the longer term. The model is discussed in the context of the Irish economy.
Keywords: Competition policy; Employment; Ireland